Flea parasites of small mammals in the Monte Desert biome in Argentina with new host and locality records - Lareschi, Marcela (2004)
Fleas associated with small mammals from the Argentinean Monte Desert, were examined. The research was carried out in Ñacuñán Biosphere Reserve (34°02´S, 67°58´W), in the Chaqueña Biogeographic Subregion of the Neotropical Region. Mammal species trapped were as follows: Rodentia, Muridae, Sigmodontinae: Akodon molinae Contreras, 1968 (N = 44), Graomys griseoflavus (Waterhouse, 1837) (N = 15), Calomys musculinus (Thomas, 1913) (N = 12), and Eligmodontia typus F. Cuvier, 1837 (N = 7); Didelphiomorphia, Didelphidae, Mamorsinae: Thylamys pusillus (Desmarest, 1804) (N = 1). A total of 236 fleas were collected: Stephanocircidae, Craneopsyllinae: Craneopsylla minerva wolffhuegeli (Rothschild, 1909); Rhopalopsyllidae, Rhopalopsyllinae: Polygenis (Polygenis) bohlsi bohlsi (Wagner, 1901), Polygenis (Polygenis) platensis cisandinus (Jordan, 1939) and Polygenis (Neopolygenis) puelche Del Ponte, 1963; Rhopalopsyllidae, Parapsyllinae: Ectinorus (Ectinorus) barrerai Jordan, 1939. High values of total mean abundance (MA = 2.99) and total prevalence (P = 73.41%) were obtained. A. molinae (MA = 3.14; P = 93.18; flea specific richness S = 5; Shannon specific diversity index H = 1.25) and G. griseoflavus (MA = 6.40; P = 100%; S = 5; H = 0.76) showed the highest values of the infestation parameters. No fleas were collected from E. typus, possibly because of its habits. Fleas associated with T. pusillus are reported for the first time. Our collections extend the western limits of the distribution of both P. (N.) puelche and P. (P.) b. bohlsi. In addition, new host species are reported for every flea species and subspecies, and seven host-flea associations are mentioned for the first time.